2021
DOI: 10.1109/tase.2020.3024291
|View full text |Cite
|
Sign up to set email alerts
|

Robot Packing With Known Items and Nondeterministic Arrival Order

Abstract: This article formulates two variants of packing problems in which the set of items is known, but the arrival order is unknown. The goal is to certify that the items can be packed in a given container and/or to optimize the size or cost of a container so that that the items are guaranteed to be packable, regardless of arrival order. The nondeterministically ordered packing (NDOP) variant asks to generate a certificate that a packing plan exists for every ordering of items. Quasionline packing (QOP) asks to gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 24 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…Y. Wu et al [12] used the genetic algorithm to solve a threedimensional bin-packing problem, considering the orientation of each object to determine the position of each container. Wang and K. Hauser [13] proposed a method for inserting irregular three-dimensional objects into containers, independent of the arrival order. A. Yasuda et al [14] applied the particle swarm optimization method to determine the position of each object offline and used a robot to perform the packing , while V. Chekanin [15] and R. Sridhar [16] showed that the genetic algorithm, which guarantees the speed and packing rate to a certain extent, is optimal for the packing problem.…”
Section: Related Workmentioning
confidence: 99%
“…Y. Wu et al [12] used the genetic algorithm to solve a threedimensional bin-packing problem, considering the orientation of each object to determine the position of each container. Wang and K. Hauser [13] proposed a method for inserting irregular three-dimensional objects into containers, independent of the arrival order. A. Yasuda et al [14] applied the particle swarm optimization method to determine the position of each object offline and used a robot to perform the packing , while V. Chekanin [15] and R. Sridhar [16] showed that the genetic algorithm, which guarantees the speed and packing rate to a certain extent, is optimal for the packing problem.…”
Section: Related Workmentioning
confidence: 99%
“…More recently, some of the authors [2] examined an optimization objective, running buffers, which is the size of the external space needed for the rearrangement task, and also examined an unlabeled setting. Similar graph structures are also used in other robotics problems, such as packing problems [19]. Deep neural networks have been also applied to detect the embedded dependency graph of objects in a cluttered environment to determine the ordering of object retrieval [9].…”
Section: Related Workmentioning
confidence: 99%
“…This section discusses existing pick-and-place manipulation pipelines, object representations for these pipelines and assumptions about the object's shape and category. Manipulation pipelines for pick-and-place: Given access to object models, previous work has addressed problems such as bin-picking [9], tight-packing [1], [2] and placement of grasped objects in clutter [3]. Most manipulation pipelines for novel objects [4], [5] focus on picking the object but do not address the problem of constrained placement.…”
Section: Related Workmentioning
confidence: 99%
“…Such scenarios occur in logistics applications, such as packing items into boxes, or in service robotics, such as inserting a book into a gap in a bookshelf. Recent work has focused on variants of this problem, such as bin-packing [1], [2] and table-top placement in clutter [3]. Nevertheless, in many cases a geometric and textured 3D model for the manipulated object is assumed to be known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation